2004
DOI: 10.1007/s00384-004-0661-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Crohn’s disease and latent celiac disease: a case report and review of the literature

Abstract: To our knowledge, this is the first report on the association of Crohn's disease and the latent form of celiac disease in the same patient. Whereas in most cases, Crohn's disease develops secondary to a pre-existing celiac disease, in our patient, latent celiac disease was diagnosed years after the onset of and therapy for Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…A previously published review of 8 cases found that CD manifested in atypical locations when in conjunction with a celiac disease diagnosis, however our study shows no significant difference in CD location in the presence of celiac disease. 27 The lack of significant differences in the clinical outcomes of patients with celiac disease and Crohn’s disease may argue against an effect of the shared risk loci between CD and celiac disease in influencing the natural history of disease. It may also be indicative that the association between immunological response seen against luminal microbial antigens and severe disease may not extend to dietary antigens such as gliadin.…”
Section: Discussionmentioning
confidence: 99%
“…A previously published review of 8 cases found that CD manifested in atypical locations when in conjunction with a celiac disease diagnosis, however our study shows no significant difference in CD location in the presence of celiac disease. 27 The lack of significant differences in the clinical outcomes of patients with celiac disease and Crohn’s disease may argue against an effect of the shared risk loci between CD and celiac disease in influencing the natural history of disease. It may also be indicative that the association between immunological response seen against luminal microbial antigens and severe disease may not extend to dietary antigens such as gliadin.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all celiac disease patients share certain HLA-DQ molecules (HLA-DQ2 or HLA-DQ8), while dietary responses lead to specific antigenic peptides in the diet that are present in wheat, rye, and barley [96]. Tursi et al [99] provided data to show a high prevalence of celiac disease among patients affected by CD, and indeed suggested that all CD patients should be started immediately on a glutenfree diet at diagnosis.…”
Section: Mhcii and Hlamentioning
confidence: 97%
“…The association of CD and CeD may be explained by shared genetic predisposition, increased gut permeability to antigens observed in both diseases [7,9,10,14,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant occurrence of CeD and CD is rare and has been reported in several case reports and series [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%